A 40 Years Old Man with Esophageal Leiomyoma - A Case Report Of Uncommon Tumor - Hoque, M Anamul; Mia, M Rahman; Islam, Kazi S; Zakirullah, SM (Chest & Heart Journal, 2021)
Leiomyoma is the most prevalent benign tumor of esophagus. It is very rare, and the incidence in autopsy series is 0.006 to 0.1%. It is mostly observed in the mid 1/3 or lower parts of esophagus. Its characteristic feature is the proliferation of the smooth muscle layer, causing circumferential thickening localized on the esophagus wall. Frequently, it is observed as a single lesion. It can be hereditary or sporadic. Half of the patients are asymptomatic. Our case was 40 years old man presented with giant esophageal leiomyoma has been presented first time in Bangladesh very few case report was been published worldwide through rare diagnosis should be keep in mind as it is benign & curable by resection. Chest Heart J. 2020; 44(1) : 52-56